Medical pharmacology at a glance - Neal, M. J. (Hoboken, NJ : Wiley-Blackwell, 2020)
'Medical Pharmacology at a Glance is recognised as an excellent starting point for pharmacology study. This international best-seller is the perfect companion for all medical and health students, providing an accessible, visual overview of pharmacology. This 9th edition has been extensively updated, with the latest guidelines, enhanced artwork, increased pedagogical features and online content. New edition of successful revision guide for medical pharmacology. Ideal for USMLE and pharmacology exam revision. Includes a companion website featuring online cases, flashcards and a list of core drugs'--Provided by publisher.
Introduction: principles of drug action -- Drug-receptor interactions -- Drug absorption, distribution and excretion -- Drug metabolism -- Local anaesthetics -- Drugs acting at the neuromuscular junction -- Autonomic nervous system -- Autonomic drugs acting at cholinergic synapses -- Drugs acting on the sympathetic system -- Ocular pharmacology -- Asthma, hay fever and anaphylaxis -- Drugs acting on the gastrointestinal tract I: peptic ulcer -- Drugs acting on the gastronintestinal tract II: motility and secretions -- Drugs acting on the kidney: diuretics -- Drugs used in hypertension -- Drugs used in angina -- Antiarrhythmic drugs -- Drugs used in heart failure -- Drugs used to affect blood coagulation -- Lipid-lowering drugs -- Agents used in anaemias -- Central transmitter substances -- General anaesthetics -- Anxiolytics and hypnotics -- Antiepileptic drugs -- Drugs used in Parkinson's disease -- Antipsychotic drugs (neuroleptics) -- Drugs used in affective disorders: antidepressants -- Opioid analgesics -- Drugs used in nausea and vertigo (antiemetics) -- Drug misuse and dependence -- Non-steroidal anti-inflammatory drugs (NSAIDs) -- Corticosteroids -- Sex hormones and drugs -- Thyroid and antithyroid drugs -- Antidiabetic agents -- Antibacterial drugs that inhibit nucleic acid synthesis: sulphonamides, trimethoprim, quinolones and nitroimidazoles -- Antibacterial drugs that inhibit cell wal systhesis: penicillians, cephalosporins and vancomycin -- Antibacterial drugs that inhibit protein synthesis: aminoglycosides, tetracyclines, macrolides and chloramphenicol -- Antifungal drugs -- Antiviral drugs -- Drugs acting on parasites I: helmniniths (worms) -- Drugs acting on parasites II: protozoa -- Drugs used in cancer -- Immunosuppressants and antirheumatoid drugs -- Poisoning -- Adverse drug reactions.
Includes bibliographical references and index.
Keywords: Pharmacological Phenomena; Pharmacology; Handbook